Mechanisms and Biomarkers of Apoptosis in Liver Disease and Fibrosis - Jayashree Bagchi Chakraborty; Fiona Oakley; Meagan J. Walsh (International Journal of Hepatology, 2012)
Liver fibrosis and cirrhosis are a major cause of morbidity and mortality worldwide. Development of the fibrotic scar is an outcome of chronic liver diseases of varying aetiologies including alcoholic liver disease (ALD) nonalcoholic liver disease (NAFLD) including non-alcoholic steatohepatitis (NASH) viral hepatitis B and C (HBV, HCV). The critical step in the development of scar is activation of hepatic stellate cells (HSCs), which become the primary source of extracellular matrix. Aberrant apoptosis is a feature of chronic liver diseases and is associated with worsening stages of fibrosis. However, apoptosis is also the main mechanism promoting the resolution of fibrosis, and spontaneous or targeted apoptosis of HSC is associated with regression of fibrosis in animal models and patients with chronic liver disease. Given the importance of apoptosis in disease progression and resolution, there is much interest in precisely delineating the mechanisms involved and also developing biomarkers that accurately reflect the underlying pathogenesis. Here, we review the mechanisms driving apoptosis in development of liver disease and use of apoptosis -related biomarkers to aid in clinical diagnosis. Finally, we will also examine the recent literature regarding new insights into mechanisms involved in apoptosis of activated HSCs as possible method of fibrosis regression.